PRZESTRZEŃ I CZAS JAKO DETERMINANTY POLITYKI GOSPODARCZEJ - Deszczyński, Przemysław (Wydział Prawa i Administracji UAM, 2009)
Space and time are the determinants o f the economic policy o f a state. Within their framework there occur far reaching changes whose common ground is evolving globalisation. In the case of space, the issue concerns the progressing loss of state sovereignty in its own territory and subjects functioning in it. This phenomenon may be described a process of deterritorialisation. In a globalisation environment, particularly at the turn o f the 20th and 21st century, the time factor has a very dynamic influence. As a result, the scope o f changes which take place within one generation exceeds all limits and calls for a redefinition of the previous development paradigm. The paper discusses those issues, referring to selected examples of creating an economic policy, with special focus on such countries as Germany, Poland, China and India.
SPACE AND TIME AS DETERMINANTS OF THE ECONOMIC POLICY